Translating erased history: Inter-Asian translation of the national Changgeuk company of Korea's Romeo and Juliet. (2nd January 2016) - Takiguchi, Ken
Abstract : As a western canonical text, Shakespeare has been translated and staged in East Asia in various ways and often adapted into traditional performance styles to counterbalance its western textual canonicity with the authenticity of eastern performative forms and styles. Negotiations between west and east, which reflect the colonial and postcolonial experiences of the region, have been a critical focus of academic investigations. What is remarkable, yet often overlooked in the west and in Asia itself, is that there were complex negotiations among East Asian translators and theatre practitioners in the early reception and translation of Shakespeare. The doubleness of Japanese colonialism – which first behaved as the "east" that absorbed western culture and later took the position of the "west" that provided advanced modern culture and technology to neighbouring countries – is the most notable element in inter-Asian cultural negotiation in the early twentieth century in general, and in the translation and staging of Shakespeare in particular. Such historicity in translation was nevertheless generally unrecognized, and even ignored, in the post–World War II cultural and social contexts in East Asia. This essay aims to explore the "erased" historicity of the translation in East Asia by examining Japanese translation of the National Changgeuk Theatre of Korea's production of Romeo and Juliet (2009) as it was published in a multilingual online digital archive called Asian Shakespeare Intercultural Archive (A|S|I|A), and to add another layer to the existing discourses on translation in this region that have mainly focused on the east-west binary. The translation strategies employed by the A|S|I|A team have sought to address the complexity of the history of translation of Shakespeare in Korea and Japan, and of discourse making in the postcolonial South Korea. The article also suggests the potential of a digital platform like A|S|I|A in capturing and representing inter-Asian negotiations thanks to its capacity to juxtapose multiple elements of translation on the screen.